Famílias sem fronteiras : um estudo dos usos e apropriações de tecnologias de informação e comunicação por famílias com membros que vivem apartados - Bianchini, Aline Feijó (2018)
The present thesis is an empirical qualitative research, with ethnographic inspirations, that seeks to understand how the communication of families with members living geographically separated from each other occurs. From the observation of the uses and appropriations of Information and Communication Technologies (ICTs), it aims to understand how these families have appropriated communicational tools to manage the distances – in the broadest sense – and the bonds among its members. Given the possibilities offered by digital technologies, we evidence that families gain new space and new resources for the management of their affective bonds. Thus, we seek to understand how this space has been configured; what resources and strategies are used and how these are employed by family members; what are the implications of this communication in a context of intensification of domestic daily life in relation to distance and how this articulates with the spaces of face-to-face and digital conviviality. For this, categories of analysis were consolidated throughout the empirical research and proposed for the observation of the object in its light. These categories – patterns of interaction, processes of appropriation of ICTs, processes of socialization and processes of signification and resignification – helped to understand the individual and family trajectories that made their members reach a common place of communication, that is, with which the dynamics of family communication occurred in certain ways, consistent with their historicalbiographical trajectories. In a context of intensification of the familiar everyday life provided by digital technologies, families without borders have communication as fundamental to their contemporary practices of intimacy, significantly reducing the relevance of the physical space for the operation and management of the domestic sphere.